2010
DOI: 10.1017/s0022112009993533
|View full text |Cite
|
Sign up to set email alerts
|

Wave processes in a viscous shock layer and control of fluctuations

Abstract: Generation and development of disturbances in a hypersonic viscous shock layer on a flat plate is studied both experimentally and numerically. The study is performed at the Mach number M∞ = 21 and the Reynolds number ReL = 1.44 × 105 and is aimed at elucidating the physical mechanisms that govern the receptivity and instability of the shock layer at extremely high hypersonic velocities. The experiments are conducted in a hypersonic nitrogen-driven wind tunnel. An electron-beam fluorescence technique, a Pitot p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…As is well known, when each of three elementary types of free-stream disturbances strikes a shock in free space, all three types of waves may emerge downstream (McKenzie & Westphal 1968). A similar process takes place when a shock is adjacent to a solid boundary, as was shown theoretically by Duck, Lasseigne & Hussaini (1995, 1997 for the supersonic flow past a wedge, and demonstrated experimentally by Maslov et al (2010) for the flat-plat boundary layer in the strongly interactive regime. In the presence of the boundary layer, the disturbance downstream also consists of reflected acoustic waves.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…As is well known, when each of three elementary types of free-stream disturbances strikes a shock in free space, all three types of waves may emerge downstream (McKenzie & Westphal 1968). A similar process takes place when a shock is adjacent to a solid boundary, as was shown theoretically by Duck, Lasseigne & Hussaini (1995, 1997 for the supersonic flow past a wedge, and demonstrated experimentally by Maslov et al (2010) for the flat-plat boundary layer in the strongly interactive regime. In the presence of the boundary layer, the disturbance downstream also consists of reflected acoustic waves.…”
Section: Introductionmentioning
confidence: 58%
“…We focus on the acoustic part of the perturbation. Vortical and entropy waves are also present (see Appendix A), but they are absorbed by a thin layer located at the outer edge of the boundary layer without entering the latter (Dong & Wu 2013; see also Maslov et al 2010, where such features were observed experimentally). The acoustic wave is governed by the (quasi-steady) Euler equations linearized about the uniform flow, among which the momentum equation in the y-direction reads…”
Section: Upper Deckmentioning
confidence: 93%
“…The study presented in this paper is of vital importance in understanding the role of nonlinear adsorption and viscous fingering in various processes where the motion of species results in the formation of nonlinear waves [31,32] or when the motion of species is encountered by nonlinear waves [33]. Our inferences could be helpful in understanding the role of adsorption parameters and viscosity ratios in chromatography applications, CO 2 capture, subsurface transport as well as in oil recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The similarity solutions of converging spherical and cylindrical shock wave problems with different equation of states (EOS) were investigated by several authors [1,6,7,9,12,15,19,22,24]. The existence and effects of the viscous forces for the similarity solutions to shock wave problems were studied by several researchers [10,17,21,28]. Landau and Lifshitz [14] and Zel'dovich and Raizer [27] have studied the entropy production in a viscous medium and developed an analytical model for the shock process based on Hugoniot curves considering the effects of viscosity and heat conduction.…”
Section: Introductionmentioning
confidence: 99%